2019
DOI: 10.1080/09575146.2019.1619670
|View full text |Cite
|
Sign up to set email alerts
|

Playing with a goal in mind: exploring the enactment of guided play in Canadian and South African early years classrooms

Abstract: Guided play, a balanced approach to involvement in play that includes child-and adult-direction in learning activities, holds great promise for children's effective and engaged learning in education. Recent studies in laboratory settings show benefits for academic and socio-emotional outcomes, while retaining a focus on child-centred exploration. Often, these studies feature an experimenter with one child or a small group. In contrast, educators in early years classrooms often need to support 20 children or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Teachers’ sharing from this study might shed light on the complex situation that EFL teachers are likely to encounter in their classrooms. According to the perspectives and practices of teachers from the present study and previous studies (Bubikova-Moan et al, 2019; Fung & Cheng, 2012; Jensen et al, 2021, etc. ), there seems to be a gap in what researchers are trying out or recommending to teachers and what teachers are doing in the classroom, as well as a gap in what western play belief is and what eastern play perception is.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Teachers’ sharing from this study might shed light on the complex situation that EFL teachers are likely to encounter in their classrooms. According to the perspectives and practices of teachers from the present study and previous studies (Bubikova-Moan et al, 2019; Fung & Cheng, 2012; Jensen et al, 2021, etc. ), there seems to be a gap in what researchers are trying out or recommending to teachers and what teachers are doing in the classroom, as well as a gap in what western play belief is and what eastern play perception is.…”
Section: Discussionmentioning
confidence: 64%
“…No matter play or play-based learning, the inconsistency between theory and practices is identified by many studies (Bubikova-Moan et al, 2019; Fung & Cheng, 2012; Jensen et al, 2021; Vorkapic & Katic, 2015). Reasons are multilayered: pressure to meet the academic goal set by school and government; parents’ concerns about play; the challenges regarding class size and time; children’s unreadiness in play and teachers’ lack of knowledge of play pedagogies (Bubikova-Moan et al, 2019).…”
Section: Play and Play-based Learning: Theoretical And Empirical Insi...mentioning
confidence: 99%
“…This entails responsivity, meaning educators tune into children's states of being in play, and intentionally meet learning goals without disrupting children's playful experience (e.g. Jensen et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the guided play research includes experimental manipulation, and very few have attempted to measure natural guided play interactions in the classroom. One study coded a recorded play session as guided play if the adult were involved in the play scenario, the child had autonomy in the play activity, and the adult extended the play beyond what would have occurred without their presence (Jensen et al, 2019). In another study through recorded classroom observations, five types of play were identified: free play, inquiry play, collaboratively created play, playful learning, and learning through games.…”
Section: Fidelity Of Implementation In the Wpmgmentioning
confidence: 99%
“…Both play and guided play can be hard to observe systematically, partly due to the wide range of definitions for both concepts. The limited research that has been conducted in more naturalistic settings, such as the classroom, tend to not publish their coding frameworks or describe them in detail (Pyle & Danniels, 2017;Wickstrom et al, 2019;Jensen et al, 2019). Previous research in laboratory settings has focused on coding adult language for math talk and their use of questions (Eason & Ramani, 2020;Linder & Emerson, 2019).…”
Section: Observationsmentioning
confidence: 99%